Deficit irrigation improves phenolic content and antioxidant activity in leafy lettuce varieties. Issue 2 (6th December 2017) - Malejane, Dunsfort N.; Tinyani, Peter; Soundy, Puffy; Sultanbawa, Yasmina; Sivakumar, Dharini
Abstract: This study investigated the effect of deficit irrigation at three management allowable depletion levels (MAD) 25%, 50%, and 75% on phytochemicals, ascorbic acid, antioxidant activity, glucose, fructose, and fresh and dry mass in two green leafy lettuce cultivars (Lollo Bionda and Vera) at harvest. Genotype response was observed during deficit irrigation on fresh and dry mass at harvest. Vera revealed similar fresh mass at MAD levels 25% and 50%. Chicoric acid, caftaric acid, and chlorogenic and caffeic acid tended to increase at 50% MAD, while kaempferol, quercetin, and myricetin increased at 75% MAD in both cultivars indicating increasing antioxidant properties. Ascorbic acid content declined with increasing MAD levels and no definite trend on β‐carotene content was noted in these cultivars with respect to MAD irrigation. Deficit irrigation at 50% and 70% increased glucose concentration in cv. Lollo Bionda. Deficit irrigation influences the abiotic stress condition that stimulates the biosynthesis of phytochemicals in plants and improves crop quality. However, deficit irrigation can affect marketable crop yield. Based on findings of this study, the lettuce cv. Vera can be recommended as a suitable cultivar for deficit irrigation (at MAD 50% levels) for improving dietary phytochemicals and crop quality without compromising fresh mass for marketing. Abstract : Lettuce cv. Vera can be recommended as a suitable cultivar for deficit irrigation (at MAD 50% levels) for improving dietary phytochemicals and crop quality without compromising fresh mass for marketing.